Campaña de lanzamiento para la nueva marca de suplementos deportivos: Mutant Store - Custodio Silva, María Fernanda (2023)
This project consists of the creation of the launch campaign for the new brand of sports supplements: Mutant Store. This brand will arrive in Peru in November with the opening of 3 stores, a website and several e-commerce channels for distribution. It seeks to revolutionize the sports supplements market by providing high-quality products guaranteeing powerful results. This work aims to achieve brand awareness among consumers. In addition, achieve 20% market share in digital channels and 2% share in offline channels at the end of the first half of launch. To achieve our objectives, we began by conducting in-depth research on our target audience and their behaviors in relation to the world of fitness and supplements. Thanks to this, it was determined that people who normally consume sports supplements are people who like to be in shape, have optimal performance and set goals. Mutant Store aims to offer powerful results with high quality products. For all this, we develop a launch strategy, where offline and online media will be used, which will help us meet the objectives.